Kepastian Hukum Gadai Tanah dalam Hukum Islam di Kabupaten Bogor - M Sulaeman Jajuli (Universitas Islam Negeri Jakarta, 2015)
Mortgage practice in Indonesian society is universal sociological phenomenon and occurs in every place. It is conventional and carries out from generation to generation. For citizen of Bogor, the mortgage land has been done since long time ago. This goes without proof documents as legal certainty. Meanwhile, academically, legal certainty is a theory that has not been developed by Islamic jurists.DOI: 10.15408/ajis.v15i2.2866